(untitled) (Global Journal of Science Frontier Research, 2018)
Workers and dealers in poultry feeds, and commercial farmers may be exposed to elevated gamma radiation doses via internal and external exposure during handling of feeds and manure in farming operations. The measurement and evaluation of internal and external exposure to gamma radiation doses due to the distribution of activity concentrations of 40 K, 226 Ra and 232 Th in starter/grower poultry feeds, finisher poultry feeds and resulting poultry manure is therefore necessary from the radiation protection point of view. The measurement was done using Sodium Iodide activated with Thallium gamma-ray spectrometer. The mean activity concentrations of 40 K, 226 Ra and 232 Th in finisher poultry manure were 382.33±67.12 8.92±3.48 39.20±5.58 respectively, and in finisher poultry feeds were 284.31±27.46 , 15.21±8.88 , 38.43±4.08 . The distribution of 226 Ra was more heterogeneous in all the samples than homogeneous distributions obtained in 40 K and 232 Th. The significant radiation exposure pathway to the farmers is from internal exposure due to inhalation of poultry and manure dust particles.